PLURALISME HUKUM SEBAGAI MODEL PEMBANGUNAN HUKUM YANG BERKEADILAN - Wandi Subroto (GoAcademica Research dan Publishing, 2022)
Legal diversity is evident in Indonesian criminal law, which is based on colonial law, and the existing social structures in the country. Furthermore, the 1945 Constitution specifies that as long as customary law groups exist, the state respects and preserves them and their historical rights. To accommodate written and unwritten conventions, diverse legal politics messo (intermediaries) implement macro-legal politics through various legislation. According to Agrarian Law, for example, there has been little recognition that customary law exists. The evolution of Indonesian law depends on recognizing and promoting the country's substantial plurality of legal systems.